Iatrogenic Pneumothorax: Procedure-Specific Risk Profile and Management Success in 23 Consecutive Cases - Dr Shagun; Dr Sunil Sharma; Dr Malay Sarkar; Dr RS Negi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Iatrogenic pneumothorax (IPX) is a well-recognised complication of pleural and lung interventions, yet contemporary data from resource-limited hospitals are sparse. Objectives: To characterise the procedural spectrum precipitating IPX, describe immediate radiographic outcomes after guideline-adapted management, and identify predictors of chest-tube requirement in a North-Indian tertiary centre. Methods: This prospective sub-analysis examined 23 consecutive IPX events identified within a 12-month pleural cohort (November 2020–October 2021). Triggers, underlying lung disease, management modality and two-hour radiographic response were recorded. Descriptive statistics with exact 95 % confidence intervals (CI) were calculated; associations with intercostal-drainage (ICD) insertion were explored using Fisher’s exact test. Results: Percutaneous procedures accounted for 78.3 % of IPX: CT-guided transthoracic needle biopsy (TTNB) for suspected lung mass 10/23 (43.5 %) and diagnostic thoracentesis 8/23 (34.8 %). Bronchoscopic tissue acquisition, including cryo-biopsy for interstitial lung disease, caused 4/23 (17.4 %). One IPX followed invasive positive-pressure ventilation. ICD was inserted in 15/23 (65.2 %); needle aspiration + oxygen succeeded in 6/23 (26.1 %); oxygen alone sufficed in 2/23 (8.7 %). Two-hour full re-expansion was achieved in 17/23 (73.9 %). Procedure-related subcutaneous emphysema occurred in 7/23 (30.4 %); no deaths were recorded. Structural lung disease (COPD/ILD) independently predicted ICD requirement (p = 0.04). Conclusions: TTNB and thoracentesis dominate IPX aetiology in this setting. Small-bore ICD secures rapid lung re-expansion with low morbidity; pre-procedural risk stratification—particularly in COPD/ILD—could further curtail chest-tube utilisation.